2022
DOI: 10.3390/sym14030490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors That Affect Asymmetric Mandibular Growth—A Systematic Review

Abstract: Facial asymmetry is a feature that occurs to a greater or lesser extent in the general population. As its severity is usually slight, facial asymmetry may not be noticeable to the patient. However, there are cases when severe facial asymmetry not only affects the facial aesthetics by distorting facial proportions, but also contributes to problems related to the function of the stomatognathic system. The nodal signalling pathway appears to be of particular importance in the process of mandibular asymmetry, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The lower facial third, especially the lower jaw, was assessed as the most asymmetric facial part [ 1 , 8 , 18 , 28 ]; in our study we also described the lower jaw as a significant source of asymmetry. Besides the external factors described above, there are gene mutations (ACTN3, PITX2) with at least a moderate degree of impact on mandibular asymmetry [ 55 ]. Another study focused on the relationship between facial asymmetry and heterozygosity in an admixed population, which showed that more heterozygous individuals exhibit lower levels of facial asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The lower facial third, especially the lower jaw, was assessed as the most asymmetric facial part [ 1 , 8 , 18 , 28 ]; in our study we also described the lower jaw as a significant source of asymmetry. Besides the external factors described above, there are gene mutations (ACTN3, PITX2) with at least a moderate degree of impact on mandibular asymmetry [ 55 ]. Another study focused on the relationship between facial asymmetry and heterozygosity in an admixed population, which showed that more heterozygous individuals exhibit lower levels of facial asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Gaur et al [ 50 ], on the other hand, found that there were only significant differences in the eruption of the maxillary central incisors and mandibular canines between the two hemiarches in children. A recent systematic review [ 51 ] analyzed the genetic factors associated with asymmetric mandibular growth, finding potential etiological factors including PITX2, ACTN3, ENPP1, and ESR1. However, to date the scientific evidence of this association is scarce; and, furthermore, no significant relationship has been found between asymmetric mandibular growth and asymmetry in dental eruption.…”
Section: Discussionmentioning
confidence: 99%
“…Although efforts were made to acquire the images with a neutral facial expression, some infants were not fully compliant, and slight facial expressions may have created bias in our measured parameters. Furthermore, gene mutations also have certain influences on the formation of craniofacial asymmetry, which was not considered and excluded from the study [36,37]. Nevertheless, these drawbacks could be improved by properly adjusting the measuring modality, collecting more participants, using a better fitting cap, and minimizing facial expressions during the scans.…”
Section: Strengths and Limitations Of 3d Stereophotogrammetrymentioning
confidence: 99%